1983
DOI: 10.1128/aac.24.1.95
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic activities of 1-(2-fluoro-2-deoxy-beta-D-arabinofuranosyl)-5-iodocytosine and -thymine alone and in combination with acyclovir and vidarabine in mice infected intracerebrally with herpes simplex virus

Abstract: The therapeutic effectiveness of two new antiviral agents, 1-(2-fluoro-2-deoxy-P-D-arabinofuranosyl)-5-iodocytosine and 1-(2-fluoro-2-deoxy-p-D-arabinofuranosyl)thymine, was compared with that of acyclovir and vidarabine. In mice inoculated intracerebrally with high 50% lethal doses of herpes simplex virus type 2, nontoxic intraperitoneal or oral treatments with the two new fluorinated antiviral agents were highly effective in reducing mortality. The two drugs were also effective when treatment was begun as la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
31
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 20 publications
4
31
0
Order By: Relevance
“…DISCUSSION Previous in vitro studies in which FIAC, FIAU, and FMAU were used have shown these compounds to be among the most potent antiherpetic agents yet described (3). Studies with mice and rabbits showed similar results (13,17). The current work is in agreement with these previous studies and adds genital herpes in guinea pigs to the list of animal models in which these fluoropyrimidine drugs are very effective.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…DISCUSSION Previous in vitro studies in which FIAC, FIAU, and FMAU were used have shown these compounds to be among the most potent antiherpetic agents yet described (3). Studies with mice and rabbits showed similar results (13,17). The current work is in agreement with these previous studies and adds genital herpes in guinea pigs to the list of animal models in which these fluoropyrimidine drugs are very effective.…”
supporting
confidence: 80%
“…FIAC and FMAU are equally active against HSV-1 and HSV-2 strains and have about the same potency as acyclovir (ACV) when assayed in rabbit kidney cells (2,17). FIAU and FMAU are more active than ACV in the treatment of HSV encephalitis in mice (13). Topical application of FIAC and FMAU is also effective in the treatment of ocular infections in rabbits (17,18).…”
mentioning
confidence: 99%
“…Thus, at the level of thymidylate kinase, IdUrd monophosphate has no selectivity for herpes simplex virus, and this may be reflected in the toxicity associated with this drug. Although previous studies have indicated that FIAC has antiviral activity in cell cultures and animals (14,16,19), the presence of FIAC triphosphate has not been reported in either in vitro or in vivo systems (13). However, metabolites of FIAC (principally 2'-fluoro-5-iodo-1-1-D-arabinofuranosyluracil) have been shown to be incorporated into cellular and viral DNAs (13).…”
mentioning
confidence: 99%
“…The compound has proven to be effective in the systemic and topical treatment of herpes simplex virus (HSV) type 2 (HSV-2) infections in both mice (11,25,31,38) and guinea pigs (39,43). Various clinical studies have demonstrated that acyclovir, when given systemically (either intravenously or perorally) or applied topically, is efficacious in the treatment of primary genital herpes (4,7,8,29,30) and, to a lesser extent, recurrent genital herpes (8,30,32,33).…”
mentioning
confidence: 99%